Body Image Scale: Evaluation of the Psychometric Properties in Three Indian Head and Neck Cancer Language Groups - Shunmugasundaram, Chindhu; Dhillon, Haryana M.; Butow, Phyllis N.; Sundaresan, Puma; Chittem, Mahati; Akula, Niveditha; Veeraiah, Surendran; Huilgol, Nagraj; Rutherford, Claudia (Frontiers in Psychology, 2022)
Background: Body image is a subjective concept encompassing a person’s views and emotions about their body. Head and neck cancer (HNC) diagnosis and treatment affects several psychosocial concepts including body image. Large numbers of HNC patients are diagnosed each year in India but there are no suitable measures in regional languages to assess their body image. This study assessed the psychometric properties of the Body Image Scale (BIS), a measure suitable for clinical and research use in HNC populations, translated into Tamil, Telugu and Hindi and compared body image distress between language groups. Methods: Translated versions of BIS were completed by HNC patients recruited from three cancer centres across India one time only. Psychometric evaluation was conducted including factor analysis using principal component analysis and internal consistency reliability using Cronbach’s alpha. Patients completed the EORTC QLQ C-30 and EORTC QLQ HN-35 measures to enable exploration of convergent and discriminant validity. ANOVA was used to calculate difference in mean values for body image. Results: Our sample included 621 HNC patients (Tamil=205, Telugu=216, Hindi=200). Factor analysis revealed a one-factor solution and Cronbach’s alpha coefficients ranged between 0.891 to 0.969 indicating good reliability. Hypothesized correlations between similar and different constructs were as expected, supporting construct validity. On the BIS, we found a statistically significant difference (F = 11.0954, P<0.05) between means of Tamil, Telugu and Hindi groups, with higher body image scores in Telugu (M = 12.86; SD = 7.65) and Hindi groups (M = 12.52; SD = 7.36) indicating more symptoms/body image distress, when compared to Tamil population (M = 9.28; SD = 10.04). Conclusions: The reliability and validity of the three translated Indian versions of the BIS were maintained, providing a method for assessing body image of HNC population worldwide speaking Tamil, Telugu and Hindi across the illness trajectory.